Sistema de Business Intelligence para apoio ao planeamento e gestão de incentivos - O caso Compete2020 - Maia, Fernando Rodrigues (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence